KONTEN DIGITAL MENDUKUNG PEMASARAN EKSPOR PT. BALI MODA BUSANA KAB. KARANGANYAR TAHUN 2024 - Praptiestrini, Praptiestrini; Sulistya, Sulistya; Budiwinarto, Kim; Trisnowati, Juni; Danarwati, Yanti Sri; Slamet, Giarti; Rohwiyati, Rohwiyati; Pujian, Dewi; Nugroho, Novie Endi (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Technology today continues to develop. Many sectors that were initially carried out directly or offline, are now switching online and utilizing existing technology, one of which is marked by the presence of digital marketing strategies. With this technological advancement, businesses are used to market their products more easily. Digital Marketing is an activity carried out to market products (promotions) with digital media, namely using internet technology. This digital marketing has the goal of attracting potential consumers appropriately. Especially with the high use of the internet among the public, this marketing is widely chosen by companies. PT. Bali Moda Busana Karanganyar Branch is one of the companies engaged in fashion and has great potential to develop the export market, especially the markets of European and American countries. Along with the development of technology and digitalization, digital product marketing has become an effective strategy to reach the international market. However, not all companies make optimal use of digital content to support the export of their products Keywords : Digital Marketing Business